2017
DOI: 10.1111/nmo.13110
|View full text |Cite
|
Sign up to set email alerts
|

Segmental colonic dilation is associated with premature termination of high‐amplitude propagating contractions in children with intractable functional constipation

Abstract: Segmental colonic dilation was associated with prematurely terminating HAPCs and may be a useful indicator of colonic dysmotility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…CM studies were performed per the respective institutions’ protocols and previously published guidelines (11,12). Both water-perfused and solid state catheters were used, with sensors spaced 2–10 cm apart.…”
Section: Methodsmentioning
confidence: 99%
“…CM studies were performed per the respective institutions’ protocols and previously published guidelines (11,12). Both water-perfused and solid state catheters were used, with sensors spaced 2–10 cm apart.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that, in children, partial propagation of HAPCs is associated with slow colonic transit 49 and segmental colonic dilation. 37 However, synchronous pressurizations at the termination of HAPCs are also hypothesized to function as a means to maintain colonic wall tone to facilitate transit in health. 45,50 Corsetti et al 45 identified pressurizations at the termination of 74% of propagating contractions in the prandial period in healthy adults.…”
Section: Our Data Included a High Prevalence Of Partially Propagatingmentioning
confidence: 99%
“…For example, if HAPCs do not propagate to the distal colon, and if the distal colon is dilated, these children could benefit from colonic resection in combination with a cecostomy. 37,54 In addition, surgical intervention may result in improved colonic motility. Following antegrade continence enemas or colonic diversion, some children with no HAPCs observed on their initial study later demonstrate HAPCs on subsequent colonic manometry studies.…”
Section: Clinical Decision-making Regarding Surgical Intervention In mentioning
confidence: 99%
See 1 more Smart Citation
“…There is no consensus yet on the precise definition of refractory constipation but failure to respond to conventional bowel management is a generally acceptable definition 2 . In patients with refractory constipation, colonic manometry (CM) testing is indicated to evaluate for colonic dysmotility from both functional and organic etiology 2–4 . CM provides information on the neuromuscular integrity of the colon by evaluating colonic muscle contractions and motility by measuring intraluminal colonic pressures throughout the cleansed colon using a manometry catheter placed endoscopically or under fluoroscopy with sensors covering the entire length of the colon from cecum to sigmoid colon 5 .…”
Section: Introductionmentioning
confidence: 99%